NITROGEN FIXING BACTERIA AZOTOBACTER AS BIOFERTILIZER AND BIOCONTROL IN LONG BEAN - Reginawanti Hindersah; Marthin Kalay; Abraham Talahaturuson; Yansen Lakburlawal (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2018)
Azotobacter is Plant Growth Promoting Rhizobacteria through the mechanism of nitrogen fixation and phytohormon production but this rhizobacteria has a role to control plant diseases. The objective of experiment was to evaluate the activity of Azotobacter as biofertilizers as well as biocontrol on long bean cultivation in damping off endemic land in Ambon city, Maluku Province. The field experiment was arranged in completely randomized block design. Inoculation of long bean by Azotobacter has been done by seed inoculation, soil inoculation before planting, and plant inoculation. Plants treated with Azotobacter received fertilizer NPK of ¾ or ½ dosage recommendation while control plants were received 100% NPK. Research showed that no differences between yield of long bean inoculated with Azotobacter sp +reduced doses of NPK with that of control plants. Any application method of Azotobacter inoculation lowered damping off diseases incidence significantly until 10 days after planting, but no effect of inoculation on late blight at 21 days after planting. This study confirmed that Azotobacter has dual activity to reduce the dose of NPK fertilizer and control damping off.